2021
DOI: 10.3389/fgene.2021.720849
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Autophagy-Related Genes of Gastric Cancer Patients on Chemotherapy

Abstract: Background: Chemotherapy resistance based on fluorouracil and cisplatin is one of the most encountered postoperative clinical problems in patients diagnosed with gastric cancer (GC), resulting in poor prognosis.Aim of the Study: This study aimed to combine autophagy-related genes (ARGs) to investigate the susceptibility patients with GC to postoperative chemotherapy.Methods: Based on The Cancer Genome Atlas (TCGA) database, gene expression data for GC patients undergoing chemotherapy were integrated and analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Autophagy is a process by which cellular material is delivered to lysosomes or vacuoles for degradation and recycling ( Chen et al, 2021b ). Cell autophagy has important regulatory roles on the cancer pathogenesis and therapeutic response ( Liu et al, 2021b ). For instance, Fusobacterium nucleatum has been found to confer chemoresistance in oesophageal squamous cell carcinoma cells by inducing autophagy ( Liu et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is a process by which cellular material is delivered to lysosomes or vacuoles for degradation and recycling ( Chen et al, 2021b ). Cell autophagy has important regulatory roles on the cancer pathogenesis and therapeutic response ( Liu et al, 2021b ). For instance, Fusobacterium nucleatum has been found to confer chemoresistance in oesophageal squamous cell carcinoma cells by inducing autophagy ( Liu et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…BRCA is the predominant malignancy affecting women globally and exhibits the highest fatality rate in female patients. ATGs exert a dual influence on BRCA, as shown in previous studies where certain ATGs have been implicated in inhibiting tumorigenesis, whereas others have been found to promote tumor characteristics in malignant mammary cells (35)(36)(37)(38). Considering the important role of autophagy in BRCA, an autophagy-related prognosis model of BRCA in TCGA dataset was constructed, and it was found that NRG2 served as a hub gene through the PPI network of DEATGs.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies suggest the vital role of autophagy in cancers, including gastric cancer. A differential expression analysis of autophagy-related genes (ARGs) in gastric cancer was carried out by Li and collaborators [ 31 ], who report a total of seven prognosis-related ARGs, including DLC1, as independent prognostic markers for gastric cancer [ 31 ]. A biomarker-based retrospective study [ 32 ] provides support for the use of the lymphocyte-to-monocyte ratio (LMR) as a novel predictor for colorectal liver cancer (CLC) treated with radiofrequency ablation (RFA).…”
Section: Discussionmentioning
confidence: 99%